Criminal activities at construction sites / Muhamad Zarif Zainal Abidin and Noraini Md Zain - Zainal Abidin, Muhamad Zarif; Md Zain, Noraini (2019)
The construction industry in Malaysia is fast growing nowadays. Along with that, this industry faces growing numbers of criminal activities at construction site such as theft, murder, bribery, vandalism and etc. The aim of this research is to identify the problems that contribute to the criminal activities and the ways to decrease criminal activities at the construction site. The research objective for this research is to identify the types of criminal activities at construction sites, to determine the contributing factors and to recommend precaution strategies to decrease the criminal activities at construction site. The questionnaire were distributed to G7 contractors in Kedah using probability sampling technique. The data were summarized into tables, diagram, charts and schedules and analysed using Statistical Package for Social Science (SPSS) software version 25. This result indicates about the criminal activities at the construction site. This paper can identify the problems that contribute to the criminal activities and the ways to decrease criminal activities at the construction site.